HRCT Spectrum in Initially COVID-19 RT-PCR Negative Patients - Aniqua Saleem , Lubna Meraj , Hira Saleem , Sharjeel Sarfraz Ahmed Sheikh , Sidra Hamid ,Huzaifa Saleem, (Journal of Rawalpindi Medical College, 2021)
Objective: To analyze radiological spectrum of HRCT in COVID-19 patients, clinically symptomatic but initially having negative RT-PCR. Study Design: Prospective cross sectional descriptive study. Place and Duration of Study: Radiology and Medicine Department, DHQ Hospital Rawalpindi, from June to November 2020 Methodology: The study included 90 patients presenting with clinical symptoms of COVID-19 but with negative RT-PCR. All patients underwent chest computed tomography (CT). Patients with positive COVID-19 RT-PCR test or serology on subsequent repeat test were included in the study. Patients having non COVID-19 HRCT features with negative RT-PCR were excluded from the study. Results: Out of 90 symptomatic, RT-PCR negative patients, 7 had normal chest CT. According to BSTI classification, 50 patients showed classic, 11 had probable and 22 had indeterminate features. Despite supportive clinical and CT features, 17 (18.89%) patients had negative RT-PCR tests on subsequent testing. Unilateral changes were in 8 (8.9%) and bilateral in 75 (83.3%). Most common finding was mixed pattern of peripherally distributed GGN and bronchocentric nodules in 37 (41.1%) patients. Consolidations were in 19 (21.1%), pure ground glass haze in 13 (14.4%), crazy paving in 4 (4.4%), fuzzy bands and arcades in 7 (7.8%), and subtle gravitational GGH in 3 (3.3%) patients. CT-SS classified 69 (76.7%) patients as mild, 10 (11.1%) as moderate and 4 (4.4%) as severe disease. Conclusions: HRCT with CTSS is an important tool for diagnosing and prognosticating COVID-19 infection despite negative RT-PCR, timely identifying and isolating COVID-19 cohorts preventing cross infection and also aiding in prompt symptomatic management.